GALICH KING COLOMAN AND AND PROCESSES OF FIRST POLITIC-RELIGIOUS OUNII IN GALICHINI IN THE FIRST FOURTH OF ХІІІ AGE - Ідзьо, В. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The problem of feudal war in Galichina resulted in fascination of this component part of Russia-Ukraine by Hungarian and Polish feudal lords turns out in the article. A basic accent is concentrated on formation of the Gadlich kingdom, the first king Coloman the First and processes of first politic-religious ounia in Galichina in the first fourth of ХІІІ age